The effect of Nickel hypersensitivity on the outcome of total knee arthroplasty and the value of skin patch testing: a systematic review - C. J. H. Peacock; H. Fu; V. Asopa; N. D. Clement; D. Kader; D. H. Sochart (Arthroplasty, 2022)
Abstract Background To assess the Nickel sensitizing potential of total knee arthroplasty (TKA), explore the relationship between hypersensitivity and clinical outcomes, and evaluate the utility of skin patch testing pre- and/or postoperatively. Materials and methods A literature search was performed through EMBASE, Medline and PubMed databases. Articles were screened independently by two investigators. The level of evidence of studies was assessed using the Oxford Centre for Evidence-Based Medicine Criteria and the quality evaluated using the Methodological Index for Non-randomized Studies and Cochrane risk-of-bias tools. Results Twenty studies met the eligibility criteria, reporting on 1354 knee arthroplasties. Studies included patients undergoing primary or revision TKA, pre- and/or postoperatively, and used patch testing to identify Nickel hypersensitivity. Prevalence of Nickel hypersensitivity ranged from 0% to 87.5%. One study compared the prevalence of Nickel hypersensitivity in the same patient group before and after surgery and noted newly positive patch test reactions in three patients (4.2%). Three studies reported lower prevalence of Nickel hypersensitivity in postoperative patients compared to preoperative ones. Seven studies suggested that hypersensitivity might cause adverse clinical outcomes, but six did not support any relationship. Seven studies recommended preoperative patch testing in patients with history of metal allergy, and nine concluded that testing may be valuable postoperatively. Conclusions Patients undergoing TKA with no prior history of metal hypersensitivity do not seem to be at an increased risk of developing Nickel hypersensitivity, and there is conflicting evidence that patients with pre-existing hypersensitivity are more likely to experience adverse outcomes. Patch testing remains the most commonly used method for diagnosing hypersensitivity, and evidence suggests preoperative testing in patients with history of metal allergy to aid prosthesis selection, and postoperatively in patients with suspected hypersensitivity once common causes of implant failure have been excluded, since revision with hypoallergenic implants may alleviate symptoms.